Editorial (American Journal of Islam and Society, 1995)
An extensive corpus of literature on the phenomenon of the Islamicmovement as a reaction to modernization and modernity has appeared duringthe past two decades. In this important category of research, Islamicdiscourse and its sociopolitical impact may be explained in tenns of thegrowing sense of alienation and exclusion generated by the changes ofmodem times. As a result, a dichotomous model of analysis has beenwidely employed in many of the recent approaches to Islam and Muslims,a model that pits the "modem," "progressive," and "rational" against the"traditional," "reactionary," and "emotional."In contrast, only a few attempts have been made to understand contemporaryIslamic discourse(s) and movements as the quintessential productsof the modernization process in the Muslim world. The case for thisalternative, though complementary, approach can be formulated on thebasis of a sociocultural analysis of the views and backgrounds of modemlslamists.For more than thirteen centuries of its history, Islam was defined intellectuallyand practically by the ulama class. This vital and pervasive socialforce, although open and accessible to various sections of society, was notwithout its own boundaries in the areas of culture, education, or piety.Progressively, of course, and for reasons that cannot be dealt with here, theulama class was transformed into an established social institution and preservedby families with long scholarly traditions and a complex networkof a particular kind of power.Twentieth-century Islamists are, by and large, graduates of modem(western?) schools who have received intensive training in modem disciplinesand methodologies. Their breeding milieu, in most cases, are modemurban centers in the Muslim world and modem social classes. Thusthey have little to do with the ancient institution of the ulama. In fact, theiradvent has marked an era of decline for the ulama class. Traditional Islam,or that of the ulama, has been and will always be a strong tributary to contemporaryIslamic thought and its world vision. But the latter's idioms,logic, symbols, structural relations, inner dynamics, and ultimate goals arenecessarily of modem geneaology.In this issue of AJISS, A. I. Tayob presents a brilliant study on the"Paradigm of Knowledge of the Modem Islamic Resurgence." Groundinghis analysis on Foucault's themes of power relations between disciplines, ...